Communication in the health area of Argentina in times of Covid-19 pandemic - K. Ramacciotti; C. Gilligan (Ибероамериканские тетради, 2022)
This article analyzes how the Covid-19 pandemic in Argentina modified communication both within the nursing sector, and with the people requiring treatment, their families or emotional ties, and institutional relations. Using a qualitative methodological strategy based on the analysis of interviews and the survey of national press, the authors organized three sections. The first section provides some notions about the characteristics of the health system and nursing education in Argentina. The second section analyzes the changes in hospital communication between nursing staff and patients with Covid-19 and, the third one describes communication experiences during the coronavirus vaccination campaign.